Morphological Polymorphism and Abundance of Camponotus compressus In Selected Habitats of Jaffna, Sri Lanka, With Molecular Confirmation - Gajapathy, K.; Sulakshana, T.; Terensan, S. (National Science and Technology Commission, 6th floor, Wing D, Sethsiripaya Stage II, Battaramulla, 2026)
Ants (Hymenoptera: Formicidae) are ecologically important insects whose success is largely attributed to social organization and caste-based morphological polymorphism. Among them, the carpenter ant Camponotus compressus is one of the most widespread species observed in both natural and human modified habitats. Despite its abundance in Sri Lanka, detailed studies on its caste specific morphology and molecular confirmation remain limited, particularly in the Jaffna Peninsula. This study examined the abundance, morphological diversity, and molecular identity of Camponotus compressus across selected sites in Jaffna from May to September 2024. Three ant species were collected from five distinct habitats, with 100 individuals per species (n = 100) sampled. Specimens were identified using standard taxonomic keys and dissected for caste-specific morphometric analysis of mouthparts. Statistical analyses were performed using one-way ANOVA. DNA was extracted, and the mitochondrial COI gene sequenced for molecular confirmation. Three species were recorded: C. compressus, Solenopsis geminata, and Oecophylla smaragdina, of which C. compressus was dominant, especially on host plants such as Cocos nucifera and Vitex negundo. Morphological analysis revealed significant caste polymorphism, with major workers showing broader mandibles for defense, minor workers exhibiting slender mandibles for foraging, queens with intermediate traits, and males with narrower mandibles reflecting reduced roles; mandible posterior width differed significantly (P 99% similarity to C. compressus reference sequences. These findings highlight C. compressus as the most abundant and morphologically diverse ant species in Jaffna, with pronounced caste polymorphism enhancing ecological versatility. They also demonstrate the value of integrating morphological and molecular approaches for robust species identification and understanding adaptive specialization in carpenter ants.
Keywords: Camponotus compressus; Morphological diversity; Jaffna